SOSIALISASI DAN DEMONSTRASI TENTANG KESEHATAN DIRI PADA ANAK-ANAK MELALUI VIDEO - Mildawati, Ratna; Prasetyo Nugroho, Bandhi; Prasetyawan, Fendy (Jurnal LENTERA, 2024)
Health is the most important part of human life, physically and spiritually healthy. However, not all children have sufficient knowledge about personal health. Elementary school age is an ideal time to train children's motor skills, including personal health. The aim is to provide education about personal health, including washing hands with soap, cleaning body parts, food and drink restrictions that can keep teeth and mouth clean. The methods used are demonstrations, counseling, using animated video media to create two-way communication and make students active in participating in activities. In this service, an instrument is used in the form of a questionnaire to measure students' knowledge and skills. The results of the socialization and demonstration that have been carried out are an increase of 40% to 90% in the knowledge indicator and an increase in skills of 35% to 80% in the skills indicator, so that this activity can be concluded to be able to increase the knowledge and skills of grade 3 students at Dawuhan Kidul I Elementary School. Explain about your own health.